Bridging a Gap between Cr(VI)-Induced Oxidative Stress and Genotoxicity in Lettuce Organs after a Long-Term Exposure - Cristina Monteiro; Sara Sario; Rafael Mendes; Nuno Mariz-Ponte; Sónia Silva; Helena Oliveira; Verónica Bastos; Conceição Santos; Maria Celeste Dias (International Journal of Agronomy)
Chromium (Cr) contamination in arable soils and irrigating water remains a priority, particularly due to the challenges posed to crop production and food safety. Long-term Cr(VI) effects remain less addressed than short-term ones, particularly regarding organ-specific genotoxic profiles. Here we used the crop Lactuca sativa growing in a protected horticultural system and irrigated for 21 days with Cr(VI) (up to 200 mg/L). Besides the oxidative stress, the genotoxicity was evaluated. Shoots and roots showed distinctive oxidative stress status and genotoxic effects, in a dose-dependent manner. While 50 mg/L stimulated antioxidant activities and no major genotoxic effects were found, plants exposed to ≥150 showed an increase of oxidative disorders, together with cytostatic and DNA damage effects, and some mitotic impairment. Leaves showed less oxidative signs at 50 mg/L, while at 150/200 mg/L the antioxidant battery was stimulated. In Cr treated plants, the highest dose increased the DNA damage, reinforcing the idea that DNA breaks were related to mitotic disorders in higher doses. In conclusion, long-term exposure data show a highly responsive root, with a quadratic response meaning higher defenses at lower Cr doses, and higher oxidative and DNA damage and cytostatic effect at a higher dose.